EFEKTIVITAS MEDIA TEKA-TEKI SILANG TERHADAP PENGENALAN KOSAKATA BAHASA INGGRIS PADA ANAK USIA 5-6 TAHUN DI TK AL-FADHLAH MINAS - Hafizhah, Salsabillah; Serli Marlina; Tisna Syafnita; Salsabillah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
English vocabulary recognition in children aged 5–6 years is often limited to pronunciation activities without an understanding of written forms. This condition impacts children's low ability to connect word sounds with written symbols. This study aims to examine the effect of using crossword puzzles on the English vocabulary recognition abilities of children aged 5–6 years at Al-Fadhlah Minas Kindergarten. The study used a quasi-experimental design with a non-equivalent control group involving two classes, each consisting of 15 children. Data analysis using an independent samples t-test showed a significant difference between the experimental and control groups (p < 0.001). The calculation of the effect size using Cohen's d produced a value of 4.11, which is categorized as very large. The results indicate that crossword puzzles provide a stronger contribution in supporting vocabulary recognition than conventional learning media